Cardiopulmonary Interactions during Positive Pressure Ventilation - John Granton (Canadian Respiratory Journal)
Positive pressure ventilation (PPV) may lead to significant hemodynamic alterations. The cardiocirculatory effects of PPV occur through alterations in the loading conditions of the right and left ventricle and are mediated by changes in intrathoracic pressures and in lung volume. However, the net effect of PPV on cardiac output and hemodynamics is not always predictable. PPV may lead to either a decrease or an increase in cardiac performance. The cardiac consequences of PPV are also dependent on baseline loading conditions and contractile function of the heart.